Role of suction/injection on electromagnetohydrodynamics natural convection flow in a porous microchannel with electroosmotic effect - Oni, Michael O.; Rilwan, Usman (Zielona Góra: Uniwersytet Zielonogórski)
This paper examined the role of suction/injection on time-dependent electromagnetohydrodynamics (EMHD) natural (free) convection flow in a vertical microchannel with electroosmotic effect. With the aid of Laplace transformation method, the governing energy and momentum equations are converted from partial differential equation (PDE) into ordinary differential equation (ODE) to obtain fluid temperature and velocity in Laplace domain.
Keywords: EMHD; natural convection; suction/injection; electroosmotic flow